Laser characteristics of NaLa(MoO₄)₂:Nd³⁺ and NaLa(Mo₀.₅W₀.₅O₄)₂:Nd³⁺ crystals - Shekhovtsov, A.N. (Functional Materials, 2012)
Pure and Nd³⁺-doped NaLa(Mo₀.₅W₀.₅)₂ and NaLa(MoO₄)₂ single crystals have been grown by the Czochralski technique. Their laser characteristics have been defined and analyzed.